Comparison of the in vitro infectivity of different strains of Theileria parva in the Muguga cocktail vaccine - Mhonjo, W.; Chaka, G.; Patel, Ekta; Kainga, H.; Kapalamula, T.; Nakao, R.; Hayashida, K.; Chatanga, E. (Cambridge University Press, 2025)
Theileria parva, a protozoan parasite, is the causative agent of East Coast fever (ECF), an economically important disease of cattle in sub-Saharan Africa. The Muguga cocktail vaccine which comprises three T. parva strains namely, Muguga, Kiambu 5, and Serengeti transformed, is used for immunisation of cattle to control ECF. However, the relative contributions of these T. parva strains to vaccine efficacy are not fully understood. This study compared the in vitro infectivity of the strains at varying concentrations of 2.75, 84.5, and 169 infected acini/ml using peripheral blood mononuclear cells (PBMCs) isolated from a bovine donor. The presence of Schizonts in cytospin smears was used to determine infectivity rates. The results indicated significant differences in the overall infectivity among the three strains at the concentrations 2.75 and 84.5 infected acini/ml but not at 169 infected acini/ml (p ≤ 0.05). These results suggest that infectivity potential reduces as the concentration increases. This was also supported by the observation that contamination increased at higher concentrations, complicating visualization and analysis. The findings reinforce the need to support the balanced composition of the Muguga cocktail vaccine to ensure broad-spectrum protection against ECF. This study emphasizes maintaining strain proportions in vaccine formulations. Future research should focus on advanced molecular techniques to refine infectivity assessments and explore strain-specific immune responses in vivo, contributing to optimized vaccine efficacy and sustainable control of ECF in endemic countries.